2021
DOI: 10.31616/asj.2019.0260
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Laterally Placed Expandable versus Static Interbody Spacers: A 1-Year Follow-Up Radiographic and Clinical Outcomes Study

Abstract: This study compared the clinical and radiographic outcomes of patients treated with expandable and static interbody spacers following minimally invasive lateral lumbar interbody fusion (MIS-LLIF) with 12-month follow-up. Overview of Literature: A common surgical option for the treatment of degenerative disk disease (DDD) is MIS-LLIF using static or expandable spacers to restore disk height (DH), neuroforaminal height (NH), and segmental lordosis. Static spacers may require excessive trialing and aggressive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…According to Marchi's criteria [25], Grades 0 and I were considered low-grade and mild subsidence, respectively, while Grades II and III were considered highgrade and severe subsidence, respectively. (2) Ten studies defined cage subsidence as disc space loss more than a specific distance on a postoperative radiograph or CT image [4,9,10,12,13,15,21,36,37,42]. Disc space loss of 1 mm, 2 mm, 3 mm, and 4 mm was applied to evaluate cage subsidence in a specific cohort.…”
Section: Subsidence Criteria and Definitionmentioning
confidence: 99%
“…According to Marchi's criteria [25], Grades 0 and I were considered low-grade and mild subsidence, respectively, while Grades II and III were considered highgrade and severe subsidence, respectively. (2) Ten studies defined cage subsidence as disc space loss more than a specific distance on a postoperative radiograph or CT image [4,9,10,12,13,15,21,36,37,42]. Disc space loss of 1 mm, 2 mm, 3 mm, and 4 mm was applied to evaluate cage subsidence in a specific cohort.…”
Section: Subsidence Criteria and Definitionmentioning
confidence: 99%
“…In 2020, Li et al completed a similar study with a one-year follow-up on 37 dual expandable cage spaces via the LLIF approach. This study was limited in that it offered no control group; however, it did note an association with mild postoperative osteopenia [ 18 ]. In 2023, Huo et al reported 48 patients receiving expandable cages with the expandable cage group notably having significantly higher rates of interbody fusion and reduced subsidence rates [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies by Frisch et al and Li et al, there was no statistically significant difference between static and expandable devices in increasing neuroforaminal height. 8,15 In the study by Frisch et al, the final intervertebral disc height after implant placement in the static group was about 4 mm more than that of the expandable group, suggesting that the static devices were possibly oversized. This alters the validity of the results because had the static devices been properly sized, the neuroforaminal area may have been significantly smaller in the static compared to the expandable group.…”
Section: Indirect Decompressionmentioning
confidence: 97%
“…High-grade device subsidence in lateral static devices is a known potential complication and has been reported between 6% and 32%. 14,15 However, several studies have shown a significant decrease in the device subsidence rate when using lateral expandable devices. In a study by Frisch et al, there was 0% subsidence in the expandable group and 16% subsidence in the static group.…”
Section: Subsidencementioning
confidence: 99%
See 1 more Smart Citation